Braiding Indigenous knowledge systems and Western-based sciences in the Alberta oil sands region: A systematic review - Alana A. E. Wilcox; Jennifer F. Provencher; Dominique A. Henri; Steven M. Alexander; Jessica J. Taylor; Steven J. Cooke; Philippe J. Thomas; Lydia R. Johnson (Canadian Science Publishing, 2023)
The braiding of Indigenous knowledge systems and Western-based sciences offers insights into ecology and has emerged as a way to help address complex environmental issues. We reviewed the publicly available ecological research involving the braiding of Indigenous knowledge systems and Western-based sciences to support collaborative work in the Alberta oil sands region of Canada. We conducted a systematic review, coding for 78 questions in six categories: (1) literature search and bibliographic information; (2) research themes; (3) study setting and design; (4) knowledge systems; (5) power relationships, colonization, and ethical considerations in research; and (6) benefits and challenges of braiding. We identified six articles that braided knowledge, with those articles focusing on environmental management and monitoring for impacts of industrial activity in northern Alberta. Researchers used a broad range of approaches to gather Indigenous knowledge and scientific data and identified multiple challenges (e.g., asymmetries of power, resource availability, and funding) to research. Our findings show that more support is needed to foster, promote, and disseminate interdisciplinary collaborative work involving braiding. Additional support is also required to address Indigenous community research needs related to the assessment of environmental impact and reclamation, as well as the understanding of ecological threats across the region.